Konfederacja pamięci: Ukraińskie postsowieckie narracje narodowe między akceptacją a odrzuceniem (zarys problemu) .......... 183 - Bobula, Joanna (Tożsamość i pamięć : konteksty kulturowe i społeczne. Studia ukrainoznawcze, 2021)
CONFEDERATION OF MEMORY: UKRAINIAN POST-SOVIET NATIONAL NARRATIVES BETWEEN ACCEPTANCE AND REJECTION (AN OUTLINE)The heterogeneity of Ukraine, which became apparent after the collapse of the USSR, is now causing a problem in finding a common, unifying vision of the past. The contradiction of the unitary national perspective with the regional versions and the polyphony of identities growing on their grounds provokes not only political fluctuations, but also the unresolved conflict of exclusive ideas about memory and the future shape of the Ukrainian national construction. The retransmission of postcolonial trauma blocks the search for alternative versions of Ukrainian identity, which results in attempts at occidentalization and de-sovietisation of eastern regions of Ukraine. Hence, in the face of the alleged defeat of these attempts, there are voices concerning the secession of “problem areas”. Based on Ukraine’s experience to date, it is legitimate to reject the ideal of national homogeneity promoted in national narratives since the 1990s in favour of a pluralistic model, perhaps at the price of redefining the denominator combining various experiences of recent decades.